Revisiting objective tests: a case study in integration at honours level - Maclaran , Pauline; Sangster , Alan (Research in Learning Technology)
Multiple-choice questions (MCQ) are widely accepted in the United States as a mode of assessment in undergraduate courses. In an environment of ever increasing class sizes, they provide a faster way to assess large groups of students, whilst also providing a way to measure deep understanding. However, in the UK there is scepticism from lecturers about the use of MCQ tests and, perhaps more significantly, from students themselves. This frequently means that someone using MCQs as a means of assessment will find both a lack of support from colleagues and resistance from students. DOI:10.1080/0968776000080207